Descriptions of two new Brazilian Subrasaca species and redescriptions of S. flavolineata (Signoret, 1855) and S. curvovittata (Stål, 1862) comb. nov. (Hemiptera: Cicadellidae: Cicadellini) - Da Silva, Roberta Dos Santos; Cavichioli, Rodney Ramiro; Mejdalani, Gabriel (Zootaxa, 2013)
The species of Subrasaca Young, 1977 with longitudinal dark brown to black stripes on the forewings are reviewed. Two new taxa are described and illustrated: S. constricta sp. nov. (from the State of Bahia, NE. Brazil, new record for the genus) and S. bimaculata sp. nov. (from the states of Minas Gerais and São Paulo, SE. Brazil and the State of Paraná, S. Brazil). Two other species from SE. Brazil are treated: S. flavolineata (Signoret, 1855) is redescribed and Tettigonia curvovittata Stål, 1862, previously considered a junior synonym of S. flavolineata, is recognized as a valid Subrasaca species (new combination) and also redescribed. In addition to the external morphology, color pattern, and male genitalia, this paper includes the first detailed description and illustrations of the female genitalia of a Subrasaca species.